2003
DOI: 10.1071/ea02200
|View full text |Cite
|
Sign up to set email alerts
|

SGS Biodiversity Theme: impact of plant biodiversity on the productivity and stability of grazing systems across southern Australia

Abstract: The relationships between productivity and plant species diversity were assessed using data from the Sustainable Grazing Systems (SGS) 10 national experiment sites. Each site applied up to 7 different management treatments. Sites varied in the amount of data available for analysis. Plant species diversity was assessed in terms of both the total and native species present at each site. More than 200 plant taxa were recorded over the period of the experiment, about one-third of which were native. In the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…Os níveis de oferta de forragem foram superiores à oferta preconizada de 16%. Esta oferta se baseou no pastejo conservativo proposto por Kemp et al (2003) para savanas em ambientes de secas periódicas, manutenção da composição botânica e otimização da produtividade, a qual compreende valores de massa de forragem entre de 2.000 a 4.000 kg de MS ha -1…”
Section: Resultsunclassified
“…Os níveis de oferta de forragem foram superiores à oferta preconizada de 16%. Esta oferta se baseou no pastejo conservativo proposto por Kemp et al (2003) para savanas em ambientes de secas periódicas, manutenção da composição botânica e otimização da produtividade, a qual compreende valores de massa de forragem entre de 2.000 a 4.000 kg de MS ha -1…”
Section: Resultsunclassified
“…Plant species richness and evenness were weakly associated with the stability of sheep production (coefficient of variation in annual carrying capacity) in New Zealand pastures (Scott 2001). Stability of forage and animal production on temperate grazing lands in southern Australia was not related to plant species richness (Kemp et al 2003).…”
Section: Ecosystem Stabilitymentioning
confidence: 91%
“…In this case the reduced variation was attributed to the inclusion of a drought‐resistant species in the complex mixture. Kemp et al. (2003) reported that overall stability in herbage accumulation was not significantly related to species richness in a study that covered ten sites across southern Australia.…”
Section: Introductionmentioning
confidence: 97%